A structural and functional analysis of Nna1 in Purkinje cell degeneration (pcd) mice - Wu, Hui-Yuan (Federation of American Societies for Experimental Biology, 2012)
The axotomy-inducible enzyme Nna1 defines a subfamily of M14 metallocarboxypeptidases, and its mutation underlies the Purkinje cell degeneration (pcd) mouse. However, the relationship among its catalytic activity, substrate specificities, and the critical processes of neurodegeneration/axon regeneration is incompletely understood. Here we used a transgenic rescue strategy targeting expression of modified forms of Nna1 to Purkinje cells in pcd mice to determine structure-activity relationships for neuronal survival and in parallel characterized the enzymatic properties of purified recombinant Nna1. The Nna1 subfamily uniquely shares conserved substrate-determining residues with aspartoacylase that, when mutated, cause Canavan disease. Homologous mutations (D1007E and R1078E) inactivate Nna1 in vivo, as does mutation of its catalytic glutamate (E1094A), which implies that metabolism of acidic substrates is essential for neuronal survival. Consistent with reports that Nna1 is a tubulin glutamylase, recombinant Nna1—but not the catalytic mutants—removes glutamate from tubulin. Recombinant Nna1 metabolizes synthetic substrates with 2 or more C-terminal glutamate (but not aspartate) residues (V(max) for 3 glutamates is ∼7-fold higher than 2 glutamates although K(M) is similar). Catalysis is not ATP/GTP dependent, and mutating the ATP/GTP binding site of Nna1 has no effect in vivo. Nna1 is a monomeric enzyme essential for neuronal survival through hydrolysis of polyglutamate-containing substrates.—Wu, H.-Y., Wang, T., Li, L., Correia, K., Morgan, J. I. A structural and functional analysis of Nna1 in Purkinje cell degeneration (pcd) mice.